A soft-chemistry approach to the synthesis of amorphous calcium ortho/pyrophosphate biomaterials of tunable composition. (February 2020) - Mayen, Laëtitia; Jensen, Nicholai D.; Laurencin, Danielle; Marsan, Olivier; Bonhomme, Christian; Gervais, Christel; Smith, Mark E.; Coelho, Cristina; Laurent, Guillaume; Trebosc, Julien; Gan, Zhehong; Chen, Kuizhi; et al.
Abstract: The development of amorphous phosphate-based materials is of major interest in the field of biomaterials science, and especially for bone substitution applications. In this context, we herein report the synthesis of gel-derived hydrated amorphous calcium/sodium ortho/pyrophosphate materials at ambient temperature and in water. For the first time, such materials have been obtained in a large range of tunable orthophosphate/pyrophosphate molar ratios. Multi-scale characterization was carried out thanks to various techniques, including advanced multinuclear solid state NMR. It allowed the quantification of each ionic/molecular species leading to a general formula for these materials: [(Ca 2+ y Na + z H + 3+ x -2y-z )(PO4 3− )1-x (P2 O7 4− )x ](H2 O)u . Beyond this formula, the analyses suggest that these amorphous solids are formed by the aggregation of colloids and that surface water and sodium could play a role in the cohesion of the whole material. Although the full comprehension of mechanisms of formation and structure is still to be investigated in detail, the straightforward synthesis of these new amorphous materials opens up many perspectives in the field of materials for bone substitution and regeneration. Statement of significance: The metastability of amorphous phosphate-based materials with various chain length often improves their (bio)chemical reactivity. However, the control of the ratio of the different phosphate entities has not been yet described especially for small ions (pyrophosphate/orthophosphate) and using soft chemistry, whereas it opens the way for the tuning of enzyme- and/or pH-driven degradation and biological properties. Our study focuses on elaboration of amorphous gel-derived hydrated calcium/sodium ortho/pyrophosphate solids at 70 °C with a large range of orthophosphate/pyrophosphate ratios. Multi-scale characterization was carried out using various techniques such as advanced multinuclear SSNMR ( 31 P, 23 Na, 1 H, 43 Ca). Analyses suggest that these solids are formed by colloids aggregation and that the location of mobile water and sodium could play a role in the material cohesion. Graphical abstract: Image, graphical abstract